Depression, Anxiety, and Stress In The Time of COVID-19 Pandemic In Kurdistan Region, Iraq - kamal, Niaz mustafa; Othman, Nasih (Kurdistan Journal of Applied Research, 2020)
The global spread of the COVID-19 pandemic, its threat to people’s health and its indirect impacts through the subsequent measures taken by governments to control the disease have led to uncertainty and huge disruption in the way people used to live with a negative impact on mental health and wellbeing. The current study estimate prevalence of the common mental health disorders among a sample of the adult population in the Kurdistan Region during the pandemic. Through an online survey using DASS-21 to measure depression, anxiety, and stress data of 548 adult participants were collected during April 2020 and analyzed. The sample was mainly from Sulaimani (89%), mean age was 37.9 (SD 13.5) and male/female ratio was 1. Prevalence of any severity levels of depression, anxiety, and stress was 45%, 47%, and 18% respectively. In regression analysis, notably female sex was a significant independent factor for higher levels of depression (coefficient 1.89, p<0.05), anxiety (coefficient 2.19, p<0.001), and stress (coefficient 1.52, p<0.05). Postgraduate education and other occupations were also significantly associated with depression (coefficient 3.81, p<0.05; coefficient 2.39, p<0.05 respectively), anxiety (coefficient 2.92, p<0.05; coefficient 4.1, p<0.001 respectively) and stress (coefficient 3.83, p<0.001; coefficient 4.1, p<0.001 respectively). The study indicates high levels of common mental health disorders during the pandemic and calls for public health measures to promote the mental health and resilience of the population.